Crotalaria L. (Fabaceae: Faboideae) in continental Southeast Asia - Ninkaew, Sakuntala; Balslev, Henrik; Pornpongrungrueng, Pimwadee; Chantaranothai, Pranom (Phytotaxa, 2017)
A revision of the 45 species of Crotalaria in Myanmar, Thailand, Laos, Cambodia, Vietnam, Malaysia and Singapore is presented. Crotalaria humifusa is recorded as new for Thailand and Vietnam while C. phyllostachya are recorded as new for Thailand only. Crotalaria collettii is reduced to synonymy under C. alata. Lectotypes are designated for Crotalaria acicularis, C. cytisoides, C. esquirolii, C. filiformis, C. goreensis, C. goreensis var. angustifolia, C. hossei, C. kerrii, C. luxurians, C. melanocarpa, C. macrostipula, C. neglecta, C. neriifolia, C. tenuifolia and C. umbellata. We provide a key to the species, nomenclature, descriptions, distribution maps, a list of specimens examined, photographs and a line drawing.